Hydro-Jet Dissection of the Cavernous Nerves Preserves Erection Function in a Radical Prostatectomy Animal Model - Jeffrey D. Campbell, MD; Husain Alenezi, MD; Ling X. DeYoung, MD; Gerald B. Brock, MD; Stephen E. Pautler, MD (Sexual Medicine, 2019)
Background: Postoperative erectile dysfunction (ED) remains a prevalent consequence of radical prostatectomy (RP) that significantly impacts patient quality of life. Water-jet technology is widely used for dissection in neurosurgical procedures but novel to urologic surgery. Aim: To establish the impact of hydro-jet dissection (HJD) of the cavernous nerves (CN) on postoperative erectile function in an animal model of RP-induced ED. Methods: 32 male Sprague-Dawley rats were randomized to 4 groups: Sham surgery (n = 8), bilateral HJD of CN (n = 8), blunt CN injury (n = 8), or stretch CN injury (n = 8). After 4 weeks, erectile function was assessed by measuring intracavernous pressure (ICP), and penile tissues were harvested for immunohistologic studies. Main Outcome Measure: The peak ICP and the area under the curve were calculated for each group. Immunohistologic studies were performed for α-smooth muscle actin and neuronal nitric oxide synthase on cross-sections of penile tissue. Results: Rats in the HJD group demonstrate a significantly higher mean peak ICP and area under the curve compared with both CN injury groups (P = .001). Postoperative erectile function in the HJD group returned to baseline function. Preservation of α-smooth muscle actin and neuronal nitric oxide synthase was observed in the HJD group compared with the other surgical trauma groups. Clinical Implications: Hydro-jet dissection used in an RP animal model maintains erectile function and offers a potential benefit that warrants further human studies. Strengths & Limitations: This is a novel animal study comparing a new technology to established CN dissection techniques. This study uses an animal model, which may not completely translate to post-RP ED in humans. Conclusion: Hydro-jet dissection of the CN during RP in an animal model is associated with significantly better postoperative erectile function when compared with other CN injury. Clinical studies are needed to further investigate the putative benefit of HJD on erectile function in patients undergoing RP.Campbell JD, Alenezi H, DeYoung LX, et al. Hydrojet Dissection of the Cavernous Nerves Preserves Erection Function in a Radical Prostatectomy Animal Model. Sex Med 2019;7:104–110. Key Words: Hydro-jet, Erectile dysfunction, Cavernous nerves, Radical prostatectomy, Intracavernous pressure